Decentralised finance: Good technology, bad finance - Maria Demertzis; Catarina Martins (Bruegel, 2023)
The emergence of cryptocurrencies/crypto assets has allowed the provision of a new form of financial services, including payments and loans, known as decentralised finance (DeFi). Crypto assets currently represent only about 1 percent of total global financial assets and it is unlikely, in its current form, that DeFi will become a substitute for the traditional financial system, for three reasons. First, while decentralisation is very innovative, in practice the technology required to replace the role of intermediary is slow and costly in terms of energy use. This has led some crypto networks to adopt more centralised solutions to the problem of verification. Second, the automaticity behind the transactions does not allow for any legal recourse. If something goes wrong, there is no way to stop or reverse a transaction once it has been initiated. It is very difficult to imagine DeFi scaling up without the ability to challenge outcomes. Third, and perhaps most importantly, DeFi is for the most part self-referential. Crypto assets are exchanged for other crypto assets without being employed in activities that stimulate economic growth by creating jobs or facilitating investment. It is not likely for DeFi to grow enough to replace traditional finance unless it helps growth. Nevertheless, the technology that enables DeFi and crypto assets, distributed ledger technology (DLT), is very innovative and has managed to remove the intermediary without compromising the safety and finality of financial transactions. Hence, it is likely that the technology behind crypto assets and DeFi will feed into the mainstream and offer efficiency gains.
Keywords: 330